Inflation pressures and times during initial resuscitation in preterm infants. Issue 8 (14th July 2017) - Bhat, Prashanth; Hunt, Katie; Harris, Christopher; Murthy, Vadivelam; Milner, Anthony D; Greenough, Anne
Abstract: Background: The optimal combination of inflation pressures and times to produce adequate expiratory tidal volumes during initial resuscitation in prematurely born infants has not been determined. The aim of this study was therefore to assess combinations of inflation pressures and times and the resulting expiratory tidal volume levels using a respiratory function monitor. Methods: Sixty‐four infants born before 34 weeks of gestation were studied. The infants were divided according to whether the inflation pressure (peak inflation pressure minus positive end expiratory pressure) was < or ≥20 cmH2 O during the first five inflations delivered by a face mask, and those groups were then subdivided according to whether the inflation time was < or ≥1.5 s. Results: Inflation pressure ≥20 cmH2 O compared with lower pressure at both inflation times produced significantly higher expiratory tidal volume. Longer compared with shorter inflation times when the inflation pressure was ≥20 cmH2 O resulted in no significant difference in expiratory tidal volume. At <20 cmH2 O inflation pressure, longer inflation time overall resulted in higher end tidal volume, but the majority of infants had a tidal volume less than the anatomical dead space. Conclusions: At higher inflation pressure, a longer inflation time was not necessary to increase expiratory tidal volume.